HUBUNGAN TINGKAT PENGETAHUAN DAN SIKAP MASYARAKAT PESISIR DENGAN KESIAPSIAGAAN MENGHADAPI BENCANA ABRASI PADA DAERAH PANTAI DI DESA CEMARA JAYA, KABUPATEN KARAWANG - Muhamad Alfian (2021)
Indonesia is a country with the second-longest coastline in the world with a length of 95,181 kilometers. The length of this coastal area can certainly have many positive and negative impacts for the people living around the coastal area or coastal communities. One of the negative impacts that can occur is the abrasion disaster. Thus, preparedness for coastal communities is needed to be able to avoid the impacts caused by the disaster. This study aims to determine the relationship between the level of knowledge and attitudes of coastal communities with preparedness to face abrasion disasters in coastal areas in Cemara Jaya village, Karawang Regency. The research method used is Cross-Sectional by using the Chi-Square test to determine the relationship between predetermined variables. The sampling technique used is probability sampling with cluster sampling type in the hamlets of Cemara Jaya 1 and 2 as many as 116 respondents. This study indicates that there is a relationship between knowledge and attitudes with abrasion disaster preparedness in Cemara Jaya village, Karawang Regency with p values of 0.027 and 0.038, which means p <0.05.